2010
DOI: 10.1245/s10434-010-1265-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-Center Long-Term Follow-Up After Intraoperative Radiotherapy as a Boost During Breast-Conserving Surgery Using Low-Kilovoltage X-Rays

Abstract: After IORT as a tumor bed boost with low-kilovoltage x-rays followed by whole-breast radiotherapy, low local recurrence and chronic toxicity rates were seen after 5-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 46 publications
9
63
1
Order By: Relevance
“…[30][31][32][33] In contrast, other studies have reported outcomes with IORT followed by WBI that appear acceptable and comparable to either WBI alone or WBI with a conventional EBRT boost. [33][34][35] As such, the task force felt the combination of IORT and WBI should be used only with caution and limited to women with higher risk features on final pathology.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…[30][31][32][33] In contrast, other studies have reported outcomes with IORT followed by WBI that appear acceptable and comparable to either WBI alone or WBI with a conventional EBRT boost. [33][34][35] As such, the task force felt the combination of IORT and WBI should be used only with caution and limited to women with higher risk features on final pathology.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…After LEX-IORT as APBI and also as a boost, low acute [6,18,19] and long term side effects and especially low chronic skin toxicities were reported [8,20,21]. In general patients with LEX-IORT as APBI were half at risk to develop higher grade late toxicities including fibrosis, breast edema, and edema of the arm, ulceration, hyperpigmentation, telangiectasia, retraction and pain [8].…”
Section: Discussionmentioning
confidence: 99%
“…In general patients with LEX-IORT as APBI were half at risk to develop higher grade late toxicities including fibrosis, breast edema, and edema of the arm, ulceration, hyperpigmentation, telangiectasia, retraction and pain [8]. After LEX-IORT as a boost, fibrosis rates are in range with standard treatments [20,21]. Further quality of life is significantly better in LEX-IORT patients in comparison to patients with whole breast radiotherapy [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…lack of geographic and temporal miss [2], applying the boost already during surgery using IORT, i.e. optimal location and optimal timing, may be superior to the standard of care usually applied as an external-beam boost [28,29,30,31]. In order to test the superiority of a TARGIT IORT boost compared to an external-beam boost, the multicentric, prospective, randomized TARGIT-B study was initiated.…”
Section: Ongoing Clinical Studies On Apbi Combined With External-beammentioning
confidence: 99%